2014
DOI: 10.1016/j.foreco.2013.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Can seed production and restricted dispersal limit recruitment in Pinus pinaster Aiton from the Spanish Northern Plateau?

Abstract: Natural regeneration faces increasing difficulties in dry forests from the Mediterranean basin, including for normally well-regenerating species such as maritime pine (Pinus pinaster Aiton). In this paper, we studied female fertility, seed dispersal and spread rates in P. pinaster from the Spanish Northern Plateau, where natural regeneration failure is a main concern for forest managers. For this purpose we periodically collected data from seed traps and trees located at two core locations across several years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 56 publications
2
15
0
6
Order By: Relevance
“…In our specific study area only 20% of the seeds were released under the crown, while in a distance of three crown radii the number of dispersed seeds is similar to that beneath the crown (Calama et al, 2015b), resulting in a close to uniform distribution of the seed rain on the soil surface. For P. pinaster median dispersal distances in the territory varied between 14.1 to 24.5 m, with maximum distances over 54 m (Juez et al, 2014). Dispersal events are concentrated in only one period, from June to August, with maximum dispersal events associated with violent summer storms.…”
Section: Seed Dispersalmentioning
confidence: 97%
See 1 more Smart Citation
“…In our specific study area only 20% of the seeds were released under the crown, while in a distance of three crown radii the number of dispersed seeds is similar to that beneath the crown (Calama et al, 2015b), resulting in a close to uniform distribution of the seed rain on the soil surface. For P. pinaster median dispersal distances in the territory varied between 14.1 to 24.5 m, with maximum distances over 54 m (Juez et al, 2014). Dispersal events are concentrated in only one period, from June to August, with maximum dispersal events associated with violent summer storms.…”
Section: Seed Dispersalmentioning
confidence: 97%
“…However, recent studies have given exact figures by counting cones on standing trees and collecting seed from traps (Ruano et al, 2015), resulting on average values around 7-24 seeds/m 2 , though showing large spatial and temporal availability (3.6 fold magnitude between years). Juez et al (2014) found that just a small fraction of mother trees are responsible for a high proportion of seed production. Ruano et al (2015) identified a climatic control over masting habit in the species, with the precipitation during the period of secondary growth of the cones positively affecting cone production.…”
Section: Flowering Fruiting and Seed Productionmentioning
confidence: 99%
“…Establishing this link is especially important in the case of tradeoffs between reproduction and growth due to the high ecological and economic importance of these biological processes. The high intraspecific variability of cone production previously reported for P. pinaster (Tapias et al, 2004;Juez et al, 2014), along with the wide fluctuation in annual weather conditions that it typically endures, highlight the potential of this species as a case study for elucidating tradeoffs in resource allocation that may have ecological and economic importance. Moreover, a strong correlation has been recently reported in this species between environmental variables and minimum tree size required for production of female reproductive structure, probably reflecting environment-dependent costs of cone production (Santos-del-Blanco et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…In the Iberian Peninsula, seed dispersal spans from May to October for P. pinaster (Juez et al. ) and from January to March for P. sylvestris (Castro et al. ).…”
Section: Methodsmentioning
confidence: 99%